Continuous treatment with guselkumab maintains clinical responses through 4 years in patients with moderate-to-severe psoriasis: results from VOYAGE 1. (17th February 2022) - Griffiths, Christopher E. M.; Papp, Kim A.; Song, Michael; Miller, Megan; You, Yin; Shen, Yaung-Kaung; Han, Chenglong; Blauvelt, Andrew
Abstract: Objectives: To evaluate the efficacy of guselkumab through four years of continuous treatment for psoriasis. Methods: In the phase 3 VOYAGE 1 trial, 837 patients with moderate-to-severe psoriasis were randomized to receive guselkumab 100 mg every-8-weeks, placebo, or adalimumab 40 mg every-2-weeks. Patients in the placebo and adalimumab groups crossed over to receive guselkumab at weeks 16/52, respectively; eligible patients received open-label guselkumab through week 204. Efficacy endpoints (i.e., PASI 75/90/100, IGA 0/1, and IGA 0) were analyzed in the guselkumab group using different methodologies: prespecified treatment failure rules (TFR, patients discontinued due to lack of efficacy, psoriasis worsening, or protocol-prohibited psoriasis treatment considered nonresponders); nonresponder imputation (NRI, patients with missing data counted as nonresponders); and As Observed (OBS, no imputation). Safety was evaluated through week 204. Results: At week 204, PASI 90 response rates were 82.2%, 68.4%, and 84.3%, respectively, based on TFR, NRI, and OBS analyses; corresponding proportions at week 52 were 79.7%, 75.5%, and 80.6%. Similarly, PASI 75, PASI 100, IGA 0/1, and IGA 0 responses were maintained from week 52 through week 204. No new safety signals were identified. Conclusions: High efficacy response rates were maintained through four years of continuous guselkumab treatment for psoriasis.